Self-Assembled Fluorinated Nanoparticles as Sensitive and Biocompatible Theranostic Platforms for 19F MRI - Havlicek, Dominik; Panakkal, Vyshakh M; Voska, Ludek; Sedlacek, Ondrej; Jirak, Daniel (Macromolecular bioscience, 2024)
Theranostics is a novel paradigm integrating therapy and diagnostics, thereby providing new prospects for overcoming the limitations of traditional treatments. In this context, perfluorocarbons (PFCs) are the most widely used tracers in preclinical fluorine-19 magnetic resonance (19F MR), primarily for their high fluorine content. However, PFCs are extremely hydrophobic, and their solutions often display reduced biocompatibility, relative instability, and subpar 19F MR relaxation times. This study aims to explore the potential of micellar 19F MR imaging (MRI) tracers, synthesized by polymerization-induced self-assembly (PISA), as alternative theranostic agents for simultaneous imaging and release of the non-steroidal antileprotic drug clofazimine. In vitro, under physiological conditions, these micelles demonstrate sustained drug release. In vivo, throughout the drug release process, they provide a highly specific and sensitive 19F MRI signal. Even after extended exposure, these fluoropolymer tracers show biocompatibility, as confirmed by the histological analysis. Moreover, the characteristics of these polymers can be broadly adjusted by design to meet the wide range of criteria for preclinical and clinical settings. Therefore, micellar 19F MRI tracers display physicochemical properties suitable for in vivo imaging, such as relaxation times and non-toxicity, and high performance as drug carriers, highlighting their potential as both diagnostic and therapeutic tools.
Keywords: nanoparticles; halogenace; zobrazování fluorovou magnetickou rezonancí; Fluorocarbons; micely; magnetická rezonanční tomografie; Halogenation; Nanoparticles; nanočástice; Theranostic Nanomedicine; Fluorine-19 Magnetic Resonance Imaging; Animals; lidé; biokompatibilní materiály; Micelles; Humans; fluor; fluorokarbony; zvířata; polymerization‐induced self‐assembly; myši; teranostická nanomedicína; Fluorine; Magnetic Resonance Imaging; theranostics; Mice; fluorine‐19; magnetic resonance; clofazimine; Biocompatible Materials